Mental health care: an analysis of the service offering in the department of Antioquia in 2025 - Dubis Marcela,; Colorado Agudelo, Julián David; Ruiz Zuluaga, Elizabet (Pensando Psicología, 2025)
This article presents an analysis of the supply of health services with emphasis on mental health in the department of Antioquia. A descriptive study was carried out considering the data of the Special Registry of Health Service Providers. Differences were found regarding the supply according to the sub-regions of the department, being the Northeast and Magdalena Medio the regions that require more attention from the territorial entities due to the low supply of mental health services. It was also found that there is more training of professionals in psychology than psychiatrists, and these are the two professions that are associated with mental health care. The planning of a hospital network system, either from the public sector or by creating mixed synergies with the private sector, is a priority to guarantee the provision of mental health services in Antioquia.
Keywords: Primary health care; mental health; psychology; psychiatry; health services